The Effect of Promotion on Financial Literacy in Increasing Buying Interest in Government Bonds - Agus Aribowo; Benny Budiawan Tjandrasa (Master of Management, School of Business and Management, Petra Christian University, 2020)
The economic development of a country as a whole can be seen from the equitable distribution of national development. To support development activities, funds are needed. The kind of funds needed is sustainable development funds to maintaineconomic development. Government Bonds (Surat UtangNegara/ SUN) are seen by the government as an alternative instrument for financing the State Budget, covering short-term cash shortages and managing the country's debt portfolio. This study aims to examine the Effect of Promotion and Financial Literacy on Buying Interest in Government Bonds (SUN). It used a descriptive survey and explanatory survey methods. The primary data collection method was obtained directly from thesource with a sample size of 100 students of Maranatha Christian University and Parahyangan University who have known about promotion and financial literacy. The distribution of the questionnaire was carried out using a non-probability sampling technique, namely purposive sampling. For data analysis, multiple linear regression statistical tool was used with a significance level of 5% for t-test and F-test. The results of this study indicate that both the partial and simultaneous tests show that promotion and financial literacy variables affect interest in the Buying Interest.